HUBUNGAN INTELEGENSI DENGAN PERILAKU NERS TINGKAT II STIKES SANTA ELISABETH MEDAN - Imelda Derang (Elisabeth Health Jurnal, 2016)
Intelligence is the ability to apply the knowledge and experiences that have been gained into the effort tasks are challenging and flexible book. Behaviour is an action that involves aspects of affective, cognitive, and psychomotor. Goal: This study aims to determine the relationship between the behavior of student nurses intelligence level II STIKes Santa Elisabeth Medan. Method: This study uses correlation with cross sectional design. The study population was all students / i Ners Level II STIKes Santa Elisabeth Medan as 65. The samples used were 65 respondents, the sampling technique in this research is using purposive sampling. The instrument of this study using questionnaire and observation sheets by using product moment test person. Result: Intelligence students as many as 30 people (46.2%) classified as having an average level of intelligence. A total of 32 people (49.2%) classified as well-behaved students. Person product moment test results obtained p value = 0.172 where a significant level of p> 0.05 so that this value proves that the absence of a relationship between the behavior of student nurses intelligence level II STIKes Santa Elisabeth Medan. Conclusion: Recommended for institutions, motivating students in balancing the behavior and intelligence.